2013
DOI: 10.1093/gbe/evt204
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History of the Clostridium difficile Pathogenicity Locus

Abstract: The symptoms of Clostridium difficile infection are caused by toxins expressed from its 19 kb pathogenicity locus (PaLoc). Stable integration of the PaLoc is suggested by its single chromosomal location and the clade specificity of its different genetic variants. However, the PaLoc is variably present, even among closely related strains, and thus resembles a mobile genetic element. Our aim was to explain these apparently conflicting observations by reconstructing the evolutionary history of the PaLoc. Phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
201
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(220 citation statements)
references
References 69 publications
(142 reference statements)
17
201
0
2
Order By: Relevance
“…Like the PaLoc reported in other clade 3 strains before [16,33,42], the PaLoc carried by the three ST201 strains discussed in this study as well as another clade 3 strain ZJCDC-S82 contained a mobile genetic element designated Tn6218 inserted between tcdE and tcdA ( Figure 2). It is suggested that the insertion of Tn6218 in PaLoc is clade-specific [16].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Like the PaLoc reported in other clade 3 strains before [16,33,42], the PaLoc carried by the three ST201 strains discussed in this study as well as another clade 3 strain ZJCDC-S82 contained a mobile genetic element designated Tn6218 inserted between tcdE and tcdA ( Figure 2). It is suggested that the insertion of Tn6218 in PaLoc is clade-specific [16].…”
Section: Discussionsupporting
confidence: 65%
“…Nucleotide sequence comparison using BlastN against the NCBI nucleotide collection database found that this this 9-kb insertion was highly homologous (99% nucleotide sequence identity) to the novel mobile genetic element Tn6218 identified in the PaLocs of clade 3 strains [33]. Correspondingly, orthologs of the four common genes (int, xis, rep, and xre) and five accessory genes (a transcription regulator gene merR; a gene encoding the oxidoreductase; the flavodoxin coding gene; an orf encoding a hypothetical protein containing the cupin domain; and the RNA polymerase σ70 coding gene) carried by Tn6218 determined before [33] were expectedly found in the 9-kb insertion contained by the ST201 strains. The TcdA and TcdB encoding genes tcdA and tcdB harbored by the ST201 strains were highly homologous to that carried by the ST1 strain or the ST11 strain.…”
Section: Sequence Analysis Of Palocmentioning
confidence: 98%
“…Also downstream of the tcdE is a partial N-acetyl-muramoyl alanine amidase of unknown significance (Monot et al, 2011). In non-toxigenic strains, the PaLoc is replaced by a 115/85-bp sequence (Braun et al, 1996;Dingle et al, 2014). Although reminiscent of a Pathogenicity Island, the PaLoc lacks any known mobility genes and repeats at its borders.…”
Section: Description Of Palocmentioning
confidence: 99%
“…Because of the difficulties with ribotyping, there has been a move towards sequencing and in silico MLST as a substitute (Dingle et al, 2011). The limited amount of whole genome sequencing-based epidemiological data currently available nearly all comes from Oxfordshire, UK (Didelot et al, 2012;Dingle et al, 2014;Dingle et al, 2011;Eyre et al, 2013), although there have been smaller scale studies performed elsewhere in the world.…”
Section: Accepted Manuscript 16mentioning
confidence: 99%
“…In nontoxigenic strains, a short, 115-bp sequence is typically found in the insertion site instead of the PaLoc (9). Recently, 75-bp and 7.2-kb sequences at the PaLoc insertion site have also been described (10,11). Horizontal gene transfer of the PaLoc has been previously shown (12), but the type of the mobile element or transfer mechanism has not been reported so far.…”
Section: Paloc-a Toxin a And B Coding Regionmentioning
confidence: 99%